Which design elements of individual quota fisheries help to achieve management objectives?. Issue 1 (22nd August 2014) - Melnychuk, Michael C; Essington, Timothy E; Branch, Trevor A; Heppell, Selina S; Jensen, Olaf P; Link, Jason S; Martell, Steven J D; Parma, Ana M; Smith, Anthony D M
Abstract: Individual quota (IQ) management systems in commercial marine fisheries are highly diverse, differing in the security, durability and exclusivity of the harvesting privilege and the transferability of quota units. This diversity in the degree of harvest rights may influence the effectiveness of IQ fisheries to meet management objectives. We conducted a global meta‐analysis of 167 stocks managed under IQs to test whether the strength of harvest rights impacts the conservation status of stocks in terms of catch, exploitation rate and biomass relative to management targets. We used non‐parametric methods to assess non‐linear relationships and linear regression models to explicitly consider interactions among predictors. Most IQ fisheries consistently met fleet‐wide quota limits (94% of stocks had recent catches below or within 10% of quotas), but only 2/3 of IQ fisheries adhered to sustainable management targets for biomass and exploitation rate (68% of stocks had exploitation rates below or within 10% of targets and 63% of stocks had biomass above or within 10% of biomass targets). Strikingly, when exclusivity of the harvesting privilege was low, exploitation rates depended on whether IQ implementation was industry‐driven (exploitation below targets) or government‐mandated (exploitation above targets). At high levels of exclusivity, exploitation rates converged to just below management targets. Transferability of quota units was associated with stock biomass closer to and slightly above target levels than stocks with non‐transferable quota. However, regional differences had the strongest effect on biomass, suggesting that other management or biological attributes of regional fishery systems have greater influence on marine populations.